The Preventive Effects of Standardized Extract of Zataria multiflora and Carvacrol on AcetaminophenInduced Hepatotoxicity in Rat - Zataria multiflora and Carvacrol and Hepatotoxicity - - Reza Mohebbati; Maryam Paseban; Farimah Beheshti; Mohammad Soukhtanloo; Mohammad Naser Shafei; Hasan Rakhshandeh; Abolfazl Khajavi Rad (Journal of Pharmacopuncture, 2018)
Objectives: The hepatotoxicity induced by Acetaminophen (AAP) mostly mediated by effect on oxidative stress parameters. The Zataria multiflora (Z.M) is an herbal medicine with well-known antioxidant effect. The aim of this study is investigation of preventive effects of Z.M and Carvacrol (CAR) on AAP-induced hepatotoxicity in rats. Methods: Rats were randomly divided into four groups including: 1) Control, 2) Acetaminophen (AAP), 3) and 4) CAR. The saline, Z.M (200 mg/kg) and CAR (20 mg/ kg) were administrated orally for 6 days, after that AAP (600 mg/kg) was administrated in the 7th day. Blood sampling was performed on the first and last days. Also, the liver tissue was removed for evaluation of Malondyaldehide (MDA), Thiol content, Superoxide dismutase (SOD) and Catalase (CAT). Total Protein (tPro), Glutamic Oxaloacetic Transaminase (GOT), Glutamic Pyruvic Transaminase (GPT) and Alkaline Phosphatase (ALP) in liver tissue were evaluated. The changes (Δ) of enzymes activities were presented. Results: The Δ GOT, Δ GPT and Δ ALP in CAR group significantly decreased compared to AAP group (P < 0.01 to P < 0.001) and Δ GPT in Z.M group was significantly reduced in comparison with AAP group (P < 0.05). Also, MDA, Thiol, SOD and CAT levels in treated groups were attenuated compared to AAP group (P < 0.05 to P < 0.001). Conclusion: Z.M and CAR have a powerful hepatoprotective effect. CAR is more effective than Z.M. Based on the results. Z.M and CAR could be potent supplementary agents against hepatotoxicity of AAP in patients.